Punishment and repentance - Tasioulas, J (Cambridge University Press, 2006)
In philosophical writings, the practice of punishment standardly features as a terrain over which comprehensive moral theories—in the main, versions of ‘consequentialism’ and ‘deontology’—have fought a prolonged and inconclusive battle. The grip of this top-down model of the relationship between philosophical theory and punitive practice is so tenacious that even the most seemingly innocent concern with the ‘consequences’ of punishment is often read, if not as an endorsement of consequentialism, then at least as the registering of a consequentialist point. But to suppose that repentance or crime prevention, for example, are goods that punishment characteristically aims to secure is hardly to endorse the maximization of some value or set of values as the fundamental criterion of moral rightness. Equally, an appeal to desert or rights in the justification of punishment does not commit one to the deontological claim that these norms have a basis independent of human interests. This suggests that the prevalence of the top-down model may owe more to the inertia of established usage, or the temptations of over-intellectualization, than one might initially have supposed.